Re-imagining anti-racism in the health sector in Aotearoa New Zealand. (30th September 2020) - Came, H; Kidd, J; McCreanor, T; Baker, M; Rodgers, B
Abstract: Background: Racism and dishonouring of te Tiriti o Waitangi are significant contributors to ethnic health inequities in Aotearoa. It is unclear how health professionals can contribute to the disruption of racism. Methods: This multi-disciplinary study draws on systems change tools, evidence from the health kaupapa Waitangi Tribunal claim (WAI 2575), a review of professional competencies documents, and focus groups with Māori and non-Māori health practitioners to identify how to strengthen anti-racism praxis in health services. The preliminary data collected in 2019 has undergone a thematic analysis and is being synthesised collaboratively with stakeholders to generate a complex continuum of anti-racism praxis. This will be applied via two site-specific action research projects. Results: The pilot study has been completed but data collection is still underway on the main study. The initial cut of a continuum of practice grouped behaviours into i) problematic, ii) variable to iii) proactive. Problematic behaviors included examples of cultural and institutional racism, Variable behavior included engagement with Te Reo me ona tikanga (Māori language and protocols), and professional development and compliance. The proactive grouping included Māori leadership and workforce, responding to Māori realities, reflective practice and critical consciousness. Conclusions: Initial findings suggest anti-racism continuum of practice may be useful to strengthen competency documents, curricula, policy and discipline-specific professional development planning. Key messages: With the persistence of institutional racism in colonial settings like Aotearoa we need to imagine new ways to pursue anti-racism. Mapping anti-racism praxis is a useful way to identify variations in practice with a view to strengthening curriculum, competencies and ultimately practice.